How do you solve 0.07 x - 0.01 y = 1.6 0.07x−0.01y=1.6 and 0.26x + 0.18 y = 16.80.26x+0.18y=16.8 using substitution?
1 Answer
Explanation:
First, we must rewrite the two equations and make sure they have an identical term. I will rewrite them as follows:
0.07x - 0.01y = 1.6 0.07x−0.01y=1.6 will become-1.26x + 0.18y = -28.8 −1.26x+0.18y=−28.8
0.26x + 0.18y = 16.8 0.26x+0.18y=16.8 will stay the same.
Now as you can see, both equations now have
We will rewrite one equation, let's use the first one, to isolate
-1.26x + 0.18y = -28.8 −1.26x+0.18y=−28.8 will become0.18y = -28.8 + 1.26x 0.18y=−28.8+1.26x
Now we can substitute this into the second equation to find the first variable.
0.26x + 0.18y = 16.8 0.26x+0.18y=16.8
0.26x + (-28.8 + 1.26x) = 16.8 0.26x+(−28.8+1.26x)=16.8
0.26x - 28.8 + 1.26x = 16.8 0.26x−28.8+1.26x=16.8
1.52x - 28.8 = 16.8 1.52x−28.8=16.8
1.52x = 45.6 1.52x=45.6
x = 30 x=30
Now that we have found the value of
Take an original question, we'll use the first one, and substitute our
0.07x - 0.01y = 1.6 0.07x−0.01y=1.6
0.07(30) - 0.01y = 1.6 0.07(30)−0.01y=1.6
2.1 - 0.01y = 1.6 2.1−0.01y=1.6
-0.01y = -0.5 −0.01y=−0.5
y = 50 y=50
So now we have solved the two equations to get